2018
DOI: 10.1080/17461391.2018.1491626
|View full text |Cite
|
Sign up to set email alerts
|

Adding omega‐3 fatty acids to a protein‐based supplement during pre‐season training results in reduced muscle soreness and the better maintenance of explosive power in professional Rugby Union players

Abstract: Evidence suggests that omega-3 fatty acid supplementation could reduce muscle soreness and maintain muscle function following eccentric exercise-induced muscle damage. The aim of this applied field study was to investigate the effectiveness of consuming a protein-based supplement containing 1546 mg of omega-3 polyunsaturated fatty acid (PUFA) (551 mg eicosapentaenoic acid (EPA) and 551 mg docosahexaenoic acid (DHA)) twice daily (FO) compared to a protein-based placebo (P) on muscle soreness, countermovement ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 53 publications
1
43
0
1
Order By: Relevance
“…In agreement with this previous DHA study, we found that the ingestion of 2.1 g/day of DHA + 240 mg/day of EPA for 10 weeks did not improve the strength deficit after an eccentric training session. However, a recent study found that omega-3 fatty acid supplementation (551 mg of EPA and 551 mg of DHA twice daily) for 5 weeks of pre-season training reduced muscle soreness and produced better maintenance of explosive power in professional Rugby Union players [40]. Moreover, an acute dose of 750 mg of EPA + 50 mg of DHA ameliorated the functional changes (jump height) following exercise-induced muscle damage [41].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this previous DHA study, we found that the ingestion of 2.1 g/day of DHA + 240 mg/day of EPA for 10 weeks did not improve the strength deficit after an eccentric training session. However, a recent study found that omega-3 fatty acid supplementation (551 mg of EPA and 551 mg of DHA twice daily) for 5 weeks of pre-season training reduced muscle soreness and produced better maintenance of explosive power in professional Rugby Union players [40]. Moreover, an acute dose of 750 mg of EPA + 50 mg of DHA ameliorated the functional changes (jump height) following exercise-induced muscle damage [41].…”
Section: Discussionmentioning
confidence: 99%
“…N -3 PUFAs supplementation was also demonstrated to reduce muscle soreness and maintain muscle function following eccentric exercise-induced muscle damage [20]. The effectiveness of consuming a protein-based supplement containing 1546 mg of n-3 PUFA (551 mg EPA and 551 mg DHA) twice daily was compared to a protein-based placebo on muscle soreness, countermovement jump performance, and psychological well-being in 20 professional Rugby Union players for five weeks of pre-season training.…”
Section: N-3 Pufas and The Health Of Skeletal Musclementioning
confidence: 99%
“…From day 20, a moderate beneficial effect of the supplement on fatigue was observed. In terms of practical relevance, the moderate beneficial effect of adding fish oil to a protein-based supplement on muscle soreness translated into the better maintenance of explosive power in elite Rugby Union players during pre-season training [20].…”
Section: N-3 Pufas and The Health Of Skeletal Musclementioning
confidence: 99%
“…Interest in the impact of the ω-3 on "recovery", or more specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the form of FO supplementation, have been investigated using an array of interventions, spanning damaging eccentric contractions [32][33][34][35], exhaustive endurance exercise [36], and immobilization [37], in trained and untrained men and women [37][38][39][40], with only limited work completed in women [35,[40][41][42]. Current data suggests, and as highlighted in a comprehensive systematic review by Heileson and Funderburk (2020), that FO supplementation likely enhances recovery and preserves strength following stressful exercise.…”
Section: Introductionmentioning
confidence: 99%